2008
DOI: 10.4141/cjas07102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing layer hen diets with selenium and vitamin E on egg quality, lipid oxidation and fatty acid composition during storage

Abstract: Mohiti-Asli, M., Shariatmadari, F., Lotfollahian, H. and Mazuji, M. T. 2008. Effects of supplementing layer hen diets with selenium and vitamin E on egg quality, lipid oxidation and fatty acid composition during storage. Can. J. Anim. Sci. 88: 475Á 483. A 7-wk trial was carried out to investigate the effect of vitamin E and inorganic and organic selenium added to hens' diet on quality and lipid stability of eggs during storage. One hundred forty-four Hy-Line W-36 hens (63-wk of age) were divided into six equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 30 publications
9
59
2
5
Order By: Relevance
“…These findings obviously contrast with the findings of other authors (Surai 2000a, b;Paton et al 2002;Mohiti-Asli et al 2008;Gajcevic et al 2009;Scheideler et al 2010;Jing et al 2015) who reported that the majority of organic Se compounds (in ng/g of wet matter) were deposited in the yolk rather than the albumen. However, if these data are corrected for dry matter with estimates of approximately 500 g/kg for the yolk and 200 g/kg for the albumen (Solomon 1991), the concentration of selenium in the albumen is greater than or equal to that in the yolk (Pappas et al 2005).…”
Section: Selenium Content In Eggs After Supplementationcontrasting
confidence: 98%
See 2 more Smart Citations
“…These findings obviously contrast with the findings of other authors (Surai 2000a, b;Paton et al 2002;Mohiti-Asli et al 2008;Gajcevic et al 2009;Scheideler et al 2010;Jing et al 2015) who reported that the majority of organic Se compounds (in ng/g of wet matter) were deposited in the yolk rather than the albumen. However, if these data are corrected for dry matter with estimates of approximately 500 g/kg for the yolk and 200 g/kg for the albumen (Solomon 1991), the concentration of selenium in the albumen is greater than or equal to that in the yolk (Pappas et al 2005).…”
Section: Selenium Content In Eggs After Supplementationcontrasting
confidence: 98%
“…According to several studies, dietary supplementation with selenium increases its abundance in eggs (Surai 2000b;Stibilj et al 2004;Benkova et al 2005;Skřivan et al 2006;Pan et al 2007;Mohiti-Asli et al 2008;Chinrasri et al 2009;Jing et al 2015).…”
Section: Selenium Content In Eggs After Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the supplementation of diets for laying hens with organic Se source appears to be an effective tool positively influencing the indicators of egg freshness [28,32]. In such a way, the enrichment of eggs with Se can improve internal egg quality and decrease susceptibility of egg yolk to lipid peroxidation during storage [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quality changes regarding storage relate to the egg content. As a result of carbonic acid dissociation, carbon dioxide is released from the egg and alkalization of the environment occurs; this subsequently causes the pH of the albumen to increase (Monira et al, 2003;Mohiti-Asli et al, 2008). The change in albumen alkalinity is also influenced by the distribution of electrostatic bonds within the ovomucin-lysozyme complex, which causes significant rarefaction (Lucisano et al, 1996).…”
Section: Introductionmentioning
confidence: 99%